IMPORTANCE OF DEVELOPMENT AND LOCALIZATION OF CONSTRUCTION MATERIALS INDUSTRY IN UZBEKISTAN (Spectrum Journal of Innovation, Reforms and Development, 2022)
In recent years, huge construction works have been carried out in our country. Construction work is being carried out rapidly in every city and village. In addition, the demand for energy-efficient, import-substituting, innovative and new types of construction materials is also increasing year by year. In particular, the demand for construction materials is growing not only in the local but also in the world markets.